Seminars in History of Ukraine: Methodological Guidelines for English-Speaking Students - Shyshkina, Yevheniia Kostyantynivna (NTU "KhPI", 2018)
The subject of the academic discipline is the basic processes of the Ukrainian national and state building, political, socio-economic and national-cultural changes, which took place in the past of the Ukrainian nation. The goals of the discipline are to improve the students' comprehension of the native history, explain the causes and consequences of political, socio-economic and national-cultural transformations that took place in different periods of Ukrainian history.
Cемінарські заняття з історії України: методичні вказівки для англомовних студентів
Keywords: methodological guidelines; history of Ukraine; different historical periods; moderate reforms